The Influence of Tax Socialization as a Catalyst in Enhancing Motor Vehicle Taxpayer Compliance: An Empirical Study at SAMSAT Serpong in South Tangerang - Surya, Hidayah Surya Masta; Litdia, Litdia (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to examine the influence of tax knowledge, taxpayer awaraness, and the tax amnesty program on motor vehicle taxpayer compliance, with tax socialization as a moderating variable. The research method used is a quantitative approach utilizing primary data collected through the distribution of questionnaires to taxpayers. This study applies accidental sampling within the probability sampling method, with a total sample of 100 registered taxpayers at the SAMSAT Serpong, determined using the slovin formula. The data were processed using SmartPLS 4 software. The results of this study indicate that tax knowledge, taxpayer awareness, and tax socialization have a positive and significant effect on motor vehicle taxpayer compliance, while the tax amnesty program has a negative effect. Tax socialization strengthens the influence of tax knowledge and taxpayer awareness on motor vehicle taxpayer compliance, but weakens the influence of the tax amnesty program on motor vehicle taxpayer compliance.